Electromagnetic simulation and microwave circuit approach of heat transport in superconducting qubits - Christoforus Dimas Satrya; Andrew Guthrie; Ilari K Mäkinen; Jukka P Pekola (Journal of Physics Communications, 2023)
The study of quantum heat transport in superconducting circuits is significant for further understanding the connection between quantum mechanics and thermodynamics, and for possible applications for quantum information. The first experimental realisations of devices demonstrating photonic heat transport mediated by a qubit have already been designed and measured. Motivated by the analysis of such experimental results, and for future experimental designs, we numerically evaluate the photonic heat transport of qubit-resonator devices in the linear circuit regime through electromagnetic simulations using Sonnet software, and compare with microwave circuit theory. We show that the method is a powerful tool to calculate heat transport and predict unwanted parasitic resonances and background.